2015
DOI: 10.1021/acs.jpcc.5b05427
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Stable Photoelectrochemical Seawater Splitting with TiO2@g-C3N4 Nanorod Arrays Decorated by Co-Pi

Abstract: Co-Pi decorated TiO 2 @graphitic carbon nitrides (g-C 3 N 4 ) nanorod arrays (denoted as CCNRs) with different mass ratios of g-C 3 N 4 have been constructed on the FTO substrate through three processes, hydrothermal growth, chemical bath deposition and electrodeposition. Firstly, TiO 2 nanorod arrays were grown onto a FTO substrate by a hydrothermal method. Secondly, g-C 3 N 4 was coated onto the TiO 2 nanorod arrays by immersing the above substrate with TiO 2 nanorod arrays into a solution of urea and then h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(95 citation statements)
references
References 68 publications
(128 reference statements)
6
89
0
Order By: Relevance
“…This enhanced performance of photo-electrodeposited films was attributed to more uniform distribution of the catalyst across the surface of the semiconductor, in a similar manner to that previously reported by Gamelin. [95][96][97] 106 The photocatalytic performance of these electrodes for the OER under 1 Sun was found to be about 30% better (at a bias of +1.5 V vs. RHE) than that of undecorated TiO 2 -gC 3 N 4 substrates, which in turn showed about 3 times the activity of TiO 2 under the same conditions. Ni-oxide electrodeposits have also been generated on semiconductor substrates for use as photoanodes for the OER.…”
Section: Electrodeposited Catalysts For Photo-driven Water Oxidationmentioning
confidence: 95%
“…This enhanced performance of photo-electrodeposited films was attributed to more uniform distribution of the catalyst across the surface of the semiconductor, in a similar manner to that previously reported by Gamelin. [95][96][97] 106 The photocatalytic performance of these electrodes for the OER under 1 Sun was found to be about 30% better (at a bias of +1.5 V vs. RHE) than that of undecorated TiO 2 -gC 3 N 4 substrates, which in turn showed about 3 times the activity of TiO 2 under the same conditions. Ni-oxide electrodeposits have also been generated on semiconductor substrates for use as photoanodes for the OER.…”
Section: Electrodeposited Catalysts For Photo-driven Water Oxidationmentioning
confidence: 95%
“…Thus, owing to the proper band level between g-C 3 N 4 and TiO 2 , g-C 3 N 4 and TiO 2 are combined together leading to the easy separation of the photo-generated electron and hole. Although there are some references about the combination of g-C 3 N 4 and TiO 2 , the morphology of TiO 2 is maily focused on nanorod1014, nanoparticles11 and nanotube151617.…”
mentioning
confidence: 99%
“…Comparing the XRD pattern of Si NWs/g-C 3 N 4 and the Si NWs, it can be concluded that the diffraction peaks at 38.5 • and 44.7 • of the Si NWs/g-C 3 N 4 sample can be attributed to the (111) and (200) crystal planes of Si. This result might be ascribed to the fact that the amount of g-C 3 N 4 was very small and well dispersed onto the surface of the Si NWs [20].…”
Section: Characterization Of Composition and Structurementioning
confidence: 99%
“…Various strategies, such as morphology modification, elemental doping, and copolymerization are subsequently applied to improve the photocatalytic performance of g-C 3 N 4 [16][17][18]. More recently, combining g-C 3 N 4 with other semiconductors, such as ZnO, TiO 2 , CuInS 2 , Bi 5 O 7 I, InVO 4 , to form a photoelectrochemical (PEC) heterogeneous electrode for water splitting has been considered an effective way to improve its photocatalytic activity [19][20][21][22][23][24][25]. However, these photoelectrodes also suffer from insufficient absorption of solar energy and poor surface area, which may restrict their practical applications.…”
Section: Introductionmentioning
confidence: 99%